Silver-clad copper material, preparation method and application thereof
By forming a silver skeleton with holes on the copper particles and forming a uniform and dense silver plating layer in the electroless plating method, the problems of high cost of silver-clad copper materials and insufficient density in the prior art are solved, and efficient oxidation resistance and electrical conductivity are achieved.
Patent Information
- Application Number
- CN202510065419.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The existing silver-clad copper materials have high raw materials and insufficient density, uniformity and oxidation resistance of the coating.
A uniform and dense silver plating layer is formed by forming a silver skeleton with holes on the copper particles and using silver salts, complexing agents and reducing agents in the electroless plating method.
It significantly improves the oxidation resistance and conductivity of silver-clad copper materials, while reducing the amount of precious metal silver, achieving cost control.
Smart Images

Figure CN119480205B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of conductive materials, and in particular to a silver-coated copper material, a preparation method and application thereof. Background Art
[0002] Silver powder is widely used in electronic pastes due to its excellent conductivity and antioxidant properties, especially in high-tech fields such as photovoltaics and the electronics industry. However, as a precious metal material, silver is relatively expensive, which increases the preparation cost and the difficulty of mass production, which to a certain extent restricts its large-scale application. In contrast, copper is cheap and abundant in reserves. Its conductivity is second only to silver, which is suitable for large-scale production. However, micro-nano copper powder has a large specific surface area and high chemical activity. During preparation and use, the surface in contact with air is easily oxidized to form an insulating oxide film, losing its original physical and chemical properties, which seriously affects the conductive properties of the material, thereby limiting its application in the electronics industry. Therefore, the preparation process of silver-coated copper powder came into being. Silver-coated copper powder is a composite material. By uniformly coating a layer of silver on the surface of copper powder, it not only significantly improves the antioxidant ability of copper powder, but also retains the excellent physical and chemical properties of copper powder. More importantly, this method reduces the use of silver and is cost-effective. However, the existing silver-coated copper powder coating has poor density and low coverage, and is prone to wear and peeling, resulting in exposure of the substrate and poor conductivity of the electrical contact material, which needs further improvement.
[0003] Common preparation methods for silver-coated copper powder include spray pyrolysis, electron beam irradiation, vapor phase spark ablation, mechanical ball milling and chemical plating. Among them, the spray pyrolysis method is to atomize the liquid precursor solution into tiny droplets, pyrolyze at high temperature, and finally form inorganic powder. Although this method can obtain uniform powder, it requires expensive spray equipment and pyrolysis furnace, which is costly. In addition, since copper is easily oxidized at high temperatures, reducing protective gases such as hydrogen and carbon monoxide are required, which increases the danger of operation and limits its application in large-scale production. The electron beam irradiation method uses an electron beam to irradiate an aqueous solution containing metal ions to produce strongly reducing hydrated electrons, which reduce the metal ions to metal powder. This method has certain advantages in raw material cost, but the electron irradiation accelerator is expensive, resulting in high initial cost of equipment commissioning. The vapor phase spark ablation method is to apply high voltage between two metal electrodes, and the metal vapor generated by spark ablation condenses to form nanoparticles. This method can directly use pure copper and pure silver as raw materials, the cost of raw materials is low, and no solvent is used in the reaction process, avoiding pollution. However, this method is still in the laboratory research stage and has not yet been industrialized. The mechanical ball milling method is to ball mill silver powder and copper powder mixed evenly in a certain proportion in a ball mill, so that the silver powder spreads on the surface of the copper powder particles to achieve the coating of the copper powder by the silver powder. This method has high production efficiency and can be mass-produced; the disadvantage is that the production investment is large, the silver consumption is high, and the cost is high.
[0004] Compared with other preparation technologies, chemical plating, as a metal surface treatment technology, has a series of significant advantages. First, its process flow is relatively simple and does not require complicated equipment and operating steps, which not only reduces production costs but also improves production efficiency. Secondly, chemical plating does not require expensive electroplating equipment and a large amount of electricity consumption, and the cost is relatively low. In addition, the chemical plating method relies on the antioxidant properties of the metallic silver coating to inhibit the oxidation of copper powder, giving the copper powder excellent antioxidant properties and high temperature stability, while the coating thickness is controllable. However, the chemical plating method also has some limitations. The most important problem is that the coating obtained by this method is usually loose and incomplete, and the density and dispersion uniformity of the coating are poor, which cannot meet the requirements of downstream industries for powder performance. In addition, in order to improve the coating effect of silver-coated copper powder, the existing technology usually pre-treats the micro-nano copper powder. First, the oil or lipid organic coating on the surface must be removed, and then it is washed with dilute acid to remove the surface oxide. After sensitization-activation treatment and other steps, the surface is silver-plated, resulting in a lengthy process flow. The preparation process requires repeated switching of the solution system, and the product needs to be repeatedly cleaned in each link, which is costly and difficult to meet the needs of industrial production. In addition, the prior art prepares silver-coated copper powder by substitution reaction. During the substitution reaction silver plating, in addition to the substitution reaction, an electrochemical reaction is also accompanied at the liquid-solid interface. This is because the micro-nano copper powder has a large specific surface area, which causes the matrix copper to be reduced to copper ions and complexed with ammonia in the plating solution to synthesize copper ammonia ions, which have a stronger adsorption capacity than silver ammonia ions, and thus preferentially adsorb on the surface of the matrix copper (i.e., silver ammonia ions ([Ag(NH 3 ) 2 ] + ) and the adsorption of the copper powder on the substrate is not enough to resist the copper ammonium ion ([Cu(NH 3 ) 4 ] 2+ ) and the adsorption of the matrix copper powder), inhibiting the progress of the replacement reaction; after that, relying on the electrochemical action, silver continues to nucleate on the already formed silver particles, resulting in poor density of the silver film, uneven coating, and low antioxidant performance, which in turn affects its conductive properties.
[0005] Therefore, there is an urgent need for a preparation method that can improve the coating density and uniformity of silver-coated copper powder while simplifying the process and reducing costs. Summary of the invention
[0006] The main purpose of the present invention is to provide a silver-clad copper material, a preparation method and application thereof, so as to solve the problems of high raw material cost, insufficient coating density, uniformity and oxidation resistance of the silver-clad copper material in the prior art.
[0007] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a silver-coated copper material is provided, comprising: a substrate and a silver layer coated on the surface of the substrate, the substrate comprising copper particles and a silver skeleton, the silver skeleton having holes, the copper particles being distributed in the holes of the silver skeleton, and the silver layer being prepared by chemical plating.
[0008] Furthermore, the diameter of the copper particles is 1-100 nm; and / or the weight percentage of the copper particles is 5-50%; and / or the weight ratio of the copper particles to the silver skeleton is (0.1-2.5):(0.5-5); and / or the pore diameter of the pores in the silver skeleton is 5-100 nm, and the specific surface area is 10-300 m 2 / g.
[0009] Furthermore, in the silver-clad copper material, the weight ratio of the substrate to the silver layer is (1~15):(0.1~5).
[0010] According to another aspect of the present invention, a method for preparing the above-mentioned silver-coated copper material is provided, comprising the following steps: step S1, first mixing a first solution including a first silver salt and an auxiliary agent, and a first alkaline solution to obtain silver-containing solid particles, and second mixing the silver-containing solid particles with a second solution including a first reducing agent and a first complexing agent to obtain a silver skeleton, wherein the silver skeleton has holes; step S2, third mixing the silver skeleton with a third solution including a copper salt, and then adding a second alkaline solution and performing a fourth mixing to obtain a fourth solution, and then adding a second reducing agent and performing a fifth mixing to fill copper particles in the holes of the silver skeleton to obtain a matrix; step S3, sixth mixing the matrix with a fifth solution including a second silver salt, a second complexing agent and a third reducing agent to perform chemical silver plating to obtain the silver-coated copper material.
[0011] Further, independently, the first silver salt and the second silver salt include one or more of silver nitrate, silver nitrite, silver acetate, silver sulfate, silver oxalate, silver methanesulfonate, silver iodide, sodium silver cyanide and dodecyl silver, with a molar concentration of 0.01-15 mol / L; and / or, the copper salt includes one or more of copper sulfate, copper chloride, copper nitrate, copper oxalate and copper acetate, with a molar concentration of 0.01-10 mol / L; and / or, independently, the first reductant, the second reductant and the third reductant include one or more of glucose, ascorbic acid, sodium ascorbate, citric acid, sodium citrate, formaldehyde, acetaldehyde, formic acid, acetic acid, hydrazine hydrate, sodium borohydride, sodium sulfite, sodium hypophosphite, sodium tartrate, sodium thiosulfate and dimethylborane, with a molar concentration of 0.001-15 mol / L; and / or, the auxiliary agent includes Na 2 SiO 3 、Na 2 CO 3and NaCl, with a molar concentration of 0.001-15 mol / L; and / or, the first alkaline solution includes one or more of an aqueous sodium hydroxide solution, an aqueous potassium hydroxide solution and an ammonia solution, with a molar concentration of 0.01-5 mol / L, and the pH of the first solution is controlled to be 5.0-14.0; and / or, the second alkaline solution includes one or more of an aqueous sodium carbonate solution, an aqueous sodium bicarbonate solution, an aqueous potassium carbonate solution, a potassium bicarbonate solution, an aqueous sodium acetate solution and an ammonia solution, with a molar concentration of 0.01-5 mol / L, and the pH of the fourth solution is controlled to be 5.0-14.0; and / or, the first complexing agent includes one or more of an ammonia solution, ethylenediamine, disodium ethylenediaminetetraacetate, monoethanolamine, diethanolamine, diisopropanolamine and N-methyldiethanolamine, with a molar concentration of 0.001-10 mol / L.
[0012] Further, in step S1, the molar ratio of the first silver salt to the auxiliary agent is (0.01-10): (0.1-15); and / or, the molar ratio of the first silver salt to the first reducing agent is (0.01-10): (10 -5 ~15); and / or, the molar ratio of the first silver salt to the first complexing agent is (0.01~10):(0.001~10).
[0013] Further, in step S1, the first mixing time is 30-180 min, the temperature is 0-80° C., the rotation speed is 100-1000 rpm, and the additive dropping rate is 1-30 mL / min; and / or, the second mixing time is 30-180 min.
[0014] Furthermore, in step S1, step S1 also includes the step of freeze-drying the silver skeleton, the freeze-drying time is 6 to 24 hours, and the temperature is -50 to -60°C.
[0015] Further, in step S2, the molar ratio of the copper salt to the weight of the silver skeleton is (0.01-10): (0.01-15) mol / g; and / or, the molar ratio of the copper salt to the second reducing agent is (0.01-10): (0.1-15).
[0016] Further, in step S2, the third mixing time is 30-180 min; and / or, the fourth mixing time is 30-180 min; and / or, the fifth mixing time is 30-180 min, and the temperature is 0-80°C.
[0017] Furthermore, step S2 also includes a step of drying the substrate, the drying time is 30-180 minutes, and the temperature is 50-80°C.
[0018] Further, in step S3, the second complexing agent includes a main complexing agent and an optional secondary complexing agent, the main complexing agent includes one or more of ammonia, ethylenediaminetetraacetic acid, ethylenediamine, diethylenetriamine, polyethylene glycol, triethylenetetramine, triethanolamine, polyethylenepolyamine and succinimide, and the molar ratio of the second silver salt to the main complexing agent is (0.01~10): (0.001~10); the secondary complexing agent includes polydopamine, hydantoin, imidazole, citric acid, sodium citrate, tartaric acid, oleic acid, oleamide, ascorbic acid, sodium pyrophosphate, aminocarboxylic acid, 1,3-dimethoxybenzene, One or more of ketones, hydroxycarboxylic acids and polyamines, the molar ratio of the second silver salt to the secondary complexing agent is (0.01~10):(0~10); and / or, the ratio of the mass of the substrate to the molar amount of the second silver salt is (0.01~10):(0.01~15) g / mol; and / or, the ratio of the mass of the substrate to the molar amount of the second complexing agent is (0.01~10):(0.001~10) g / mol; and / or, the ratio of the mass of the substrate to the molar amount of the third reducing agent is (0.01~10):(0.1~15) g / mol.
[0019] Furthermore, in step S3, the temperature of the sixth mixing is 0-80°C and the time is 30-180 min; and / or, step S3 also includes washing the silver-coated copper material until the conductivity of the silver-coated copper material washing mother liquor is ≤20 μS / cm, and then performing a drying step.
[0020] Further, independently, the first solution, the second solution, the third solution, and the fifth solution include an organic solvent and water, and the organic solvent includes one or more of methanol, ethanol, propanol, ethylene glycol, isopropanol, acetone, N,N-dimethylformamide, N,N-dimethylacetamide and diethylformamide, and the molar concentration is 0.001-10 mol / L; and / or, independently, the first solution, the second solution, the third solution, and the fifth solution include a dispersant, and the dispersant includes one or more of polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone, methylcellulose, polyacrylic acid, sodium sulfosuccinate, sodium lauryl sulfate, sodium lauryl sulfonate, Tween 80, sodium stearate, ethanolamine, fatty alcohol polyoxyethylene ether, octylphenol polyoxyethylene ether 10, dodecyl tetraethylene glycol ether and nonylphenol polyoxyethylene ether 10, and the molar concentration is 10 -5 ~5mol / L.
[0021] According to another aspect of the present invention, there is provided application of the above silver-clad copper material in the photovoltaic and electronic industry fields.
[0022] The present invention utilizes the pore structure of the silver skeleton and the distribution of copper particles to achieve the separation of silver coating nucleation and growth, ensure the uniformity and compactness of the silver coating growth, and thus improve the oxidation resistance and electrical conductivity of the silver-coated copper material. While ensuring the material performance, the amount of precious metal silver is greatly reduced, achieving cost control. When the silver-coated copper material of the present invention is used in the photovoltaic and electronic industries, the cost of raw materials can be significantly reduced, the service life of the raw materials can be increased, and large-scale use is facilitated. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0024] Figure 1 A schematic diagram of the preparation process of the silver-clad copper material according to Example 1 of the present invention is shown;
[0025] Figure 2 The SEM image of the silver-clad copper material of Example 1 of the present invention is shown;
[0026] Figure 3 A graph showing the specific surface area of the silver skeleton in the silver-clad copper material of Example 1 of the present invention; and
[0027] Figure 4 The pore size distribution diagram of the silver skeleton in the silver-clad copper material of Example 1 of the present invention is shown.
[0028] The following reference numerals are used herein:
[0029] 1. Silver skeleton; 2. Copper particles; 3. Matrix; 4. Silver particles; 5. Epitaxial layered / island silver particles; 6. Silver plating; 7. Silver-coated copper material. DETAILED DESCRIPTION
[0030] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0031] As described in the background of the present invention, the prior art has the problems of high raw material cost of silver-coated copper materials, insufficient density, uniformity and oxidation resistance of the coating. In order to solve the above problems, in a typical embodiment of the present invention, a silver-coated copper material is provided, comprising: a substrate and a silver layer coated on the surface of the substrate, the substrate comprising copper particles and a silver skeleton, the silver skeleton having holes, the copper particles being distributed in the holes of the silver skeleton, and the silver layer being prepared by chemical plating.
[0032] In the prior art, the matrix of the silver-coated copper material is usually micro-nano copper powder. However, in the process of preparing the silver-coated copper material (such as silver-coated copper powder) with micro-nano copper powder as the matrix, a lipophilic surface modifier is usually used to modify the surface of the micro-nano copper powder to inhibit oxidation, thereby effectively protecting the micro-nano copper powder and changing its surface energy. However, this process is easy to mix with impurities such as oil, lipid organic matter, etc., and a cleaning agent (NaOH, ethanol, degreasing agent, etc.) is required to pre-treat and clean the micro-nano copper powder. During the pre-cleaning process, the strong alkali will chemically react with the surface of the micro-nano copper powder, causing the surface structure of the micro-nano copper powder to easily change (such as corrosion of the copper powder surface), thereby destroying the active sites on the surface of the micro-nano copper powder, so that the activity of the pre-treated micro-nano copper powder is reduced; in addition, if the (organic) protective layer on the surface of the micro-nano copper powder cannot be effectively removed, it will affect the silver plating process to a certain extent, resulting in a slow reaction process, which is not conducive to the subsequent preparation of silver-coated copper powder by chemical plating.
[0033] In the silver-clad copper material of the present application, the matrix is composed of copper particles and a silver skeleton, wherein the silver skeleton contains holes, and the copper particles are distributed in these holes. The core advantage of this matrix structure comes from the capillary effect in the holes of the silver skeleton, which can promote the raw materials of the copper particles (such as copper salt solution) to penetrate and fill the pores, creating favorable conditions for the subsequent chemical reduction deposition process, so that the copper particles can not only be adsorbed on the surface of the silver skeleton, but also penetrate into its pores. This mechanism can not only ensure the effective filling of copper particles, but also provide abundant nucleation active sites for the formation of the outer silver coating, which is conducive to significantly improving the nucleation rate of the coating and realizing the refinement of the silver coating grains, thereby strengthening the coating structure and making its surface smooth, flat and dense.
[0034] It should be noted that the growth process of the silver layer can be divided into two key stages: nucleation and crystal nucleus growth. In the traditional preparation method, these two stages are usually carried out simultaneously, resulting in the growth of silver nanocrystal nuclei at different times and environments, thereby affecting the uniformity of the particle size of the silver particles in the silver layer, resulting in poor compactness of the silver coating. In contrast, the present application combines the silver skeleton with the copper particles to first form a matrix with a porous core-shell structure, and then forms a silver coating on the surface of the substrate by chemical plating. During the deposition process of the coating, the exposed silver skeleton can be used as a heterogeneous nucleation active site under the action of the surface effect, which can induce the aggregation of the silver atoms generated by the post-reduction to form epitaxial layered / island-shaped silver particles, and realize the "layer-island" mixed growth mode of the silver coating. This design cleverly separates the nucleation of silver nanocrystals from the crystal growth process, which conforms to the Lamer model of "explosive nucleation and slow growth", thereby ensuring the uniformity of the growth of the silver coating.
[0035] During the formation of the silver coating, the silver nanocrystal core grows in a "layer-island" mixed mode, that is, the copper on the surface of the silver skeleton undergoes a replacement reaction with the silver ions in the reaction solution system of the chemical silver plating process, so that the Ag atoms are deposited on the copper surface to coat the copper; at the same time, the exposed silver skeleton has good wettability with the deposited silver nanocrystals, which can not only provide nucleation active sites for the silver nanocrystals, but also easily bond with the Ag atoms; therefore, during the silver plating process, the silver nanocrystals extend and spread on the substrate surface in a two-dimensional layered growth mode from the initial stage of nucleation. After the silver particles aggregate and grow in layers to a certain thickness, the growth mode will change from a layered mode to an island mode. With the continuous supply of silver salt, this process repeats itself, the thickness of the silver coating gradually increases, and a continuous coating layer is gradually formed, and finally a complete coating structure is formed. This "layer-island" mixed growth mode can not only increase the coating rate of the coating, but also significantly improve the coating effect of the coating, thereby greatly improving the density and oxidation resistance of the silver-clad copper material, while reducing the amount of precious metals used and improving the conductivity.
[0036] In addition, during the process of chemically plating the silver layer on the substrate surface, when the substrate of the present application is immersed in the raw material of the silver layer (such as the fifth solution including the second silver salt, the second complexing agent and the third reducing agent in the present application), the silver ions are attached to the activated surface of the exposed silver skeleton of the substrate, and the direct replacement reaction can be weakened under the action of the reducing agent. This is because the reducing agent can be Ag + Provide electrons to reduce it to silver and deposit it directly on the surface of the substrate to form a silver coating. + A substitution reaction will occur, that is, when Ag + When it reaches the copper surface inside the silver skeleton, it will undergo a replacement reaction with the Cu atoms. Due to the spatial physical confinement effect of the silver skeleton, it can significantly reduce the Ag + The diffusion mass transfer rate can reduce the rate of the replacement reaction. At the same time, the complexing agent can react with Ag + Combined to form a complex, the concentration of silver ions in the plating solution is regulated, the chemical reaction rate is slowed down, and the growth rate of the crystal nucleus during the silver plating process is regulated, and the uniformity and coverage of the silver layer are improved. In addition, according to the thermodynamic parameters of chemical silver plating, copper is more chemically active than silver, and a replacement reaction can occur in the plating solution to obtain a silver layer; however, this phenomenon mainly occurs in the initial reaction stage (the aqueous solution does not contain Cu 2+ or Cu 2+ The concentration is very low), the replacement reaction is dominant, and as the reaction continues, under the complexation effect, the free Ag in the reaction system + will be gradually released, and its concentration in the plating solution will gradually increase, so that the reduction reaction gradually becomes dominant. For ease of understanding, the reactions involved in chemical plating are listed here:
[0037] Ag ++e - =Ag (E Ɵ =0.799V) (1)
[0038] Cu+2Ag + =2Ag+Cu 2+ (E Ɵ =1.261V) (2)
[0039] Cu 2+ +2e - =Cu (E Ɵ =0.337V) (3)
[0040] In summary, the present application utilizes the pore structure of the silver skeleton and the distribution of copper particles to separate the nucleation and growth of the silver coating, thereby ensuring the uniformity and density of the growth of the silver coating, thereby improving the oxidation resistance and electrical conductivity of the silver-clad copper material. While ensuring the material performance, the amount of precious metal silver can be greatly reduced to achieve cost control.
[0041] In a preferred embodiment, in the silver-coated copper material, the diameter of the copper particles is 1-100 nm; and / or the weight percentage of the copper particles is 5-50%; and / or the weight ratio of the copper particles to the silver skeleton is (0.1-2.5):(0.5-5), preferably 1:(0.5-3); and / or the pore size of the pores in the silver skeleton is 5-100 nm, preferably 38-60 nm, and the specific surface area is 10-300 m 2 / g, preferably 19~30m 2 / g. Under the above conditions, the content of copper particles is higher, which is more conducive to reducing the cost of silver-clad copper materials, and the silver skeleton has a richer pore structure, which is more conducive to reducing the dissolution of copper and the negative effects of copper ions on the plating stage.
[0042] In a preferred embodiment, in the silver-coated copper material, the weight ratio of the substrate to the silver layer is (1-15): (0.1-5), preferably (2-5): 1, and more preferably (2.52-2.56): 1. In a preferred embodiment, the silver-coated copper material is first heated to 500°C, kept at a constant temperature for 30 min in an air atmosphere, and then cooled, and the weight gain rate is ≤8.8wt%, preferably 6-8.77wt%; the resistivity is ≤4×10 -4 Ω·cm, preferably 2×10 -4 ~3.5×10 -4 Ω·cm. Under the above conditions, the conductivity of silver-clad copper material is better and the cost is lower.
[0043] In another typical embodiment of the present invention, a method for preparing the above-mentioned silver-coated copper material is also provided, comprising the following steps: step S1, mixing a first solution including a first silver salt and an auxiliary agent and a first alkaline solution for a first time to obtain silver-containing solid particles, and mixing the silver-containing solid particles with a second solution including a first reducing agent and a first complexing agent for a second time to obtain a silver skeleton, wherein the silver skeleton has holes; step S2, mixing the silver skeleton with a third solution including a copper salt for a third time, then adding a second alkaline solution and mixing for a fourth time to obtain a fourth solution, then adding a second reducing agent and mixing for a fifth time to fill copper particles in the holes of the silver skeleton to obtain a matrix; step S3, mixing the matrix with a fifth solution including a second silver salt, a second complexing agent and a third reducing agent for a sixth time to perform chemical silver plating to obtain the silver-coated copper material.
[0044] In the preparation method of the present application, first, the product of the double decomposition reaction of the silver salt is expanded to act as a soft template to synthesize a silver skeleton with holes; then, the silver skeleton undergoes an in-situ reduction reaction with a copper salt and a reducing agent under alkaline conditions to fill the silver skeleton with copper particles; then, the substrate is chemically silver-plated to form an outer-coated silver layer. In this process, the structure of the silver-coated copper material is optimized, that is, the porous structure of the silver skeleton is filled with copper particles to form a substrate, and in the process of chemical silver plating, the active surface of the substrate is used to provide nucleation sites for the silver coating, thereby improving the nucleation rate of the coating, refining the grains, and strengthening the silver coating, so that the coating surface is smooth and flat, the overall density is improved, and the conductive performance is improved.
[0045] It should be noted that after sufficient research, the inventors found that the current mainstream methods for preparing porous materials are mainly dealloying and template methods (templates can be hard templates and soft templates according to the material). The dealloying method for preparing nanoporous metals usually requires the introduction of a second metal phase, and the second metal is removed by acid / base etching, which easily causes a certain amount of loss and waste of the first metal, and the process is cumbersome. The template method usually requires the use of expensive template agents, which are prone to pollution during the removal of the template agent, and are almost impossible to reuse, which greatly increases the production cost and limits its application. In step S1 of the present application, the double decomposition reaction expansion product of the silver salt acts as a soft template, that is, the method using the reaction intermediate product as a template, gets rid of the dependence on the conventional template method, and has the advantages of simple synthesis step process flow, low production cost and easy large-scale preparation.
[0046] In order to clearly describe the mechanism, illustratively, in step S1, the silver salt is silver nitrate, the soft template is an intermediate product in the synthesis process (silver tetrasilicate), and the auxiliary agent is Na 2 SiO 3 solution, the first alkaline solution is NaOH aqueous solution, and the reducing agent is NaBH 4 , and / or, formic acid, the chemical reactions involved are as follows:
[0047] 10AgNO 3 +4Na 2 SiO 3 +2NaOH=Ag 10 Si 4 O 13 ↓+10NaNO 3 +H 2 O (4)
[0048] 2Ag 10 Si 4 O 13 +5NaBH 4 +20NaOH=20Ag↓+5NaB(OH) 4 +2Na 10 Si 4 O 13 +10H 2 ↑ (5)
[0049] Ag + +OH - =AgOH and / or,
[0050] 2AgOH=Ag 2 O↓+H 2 O and / or,
[0051] 2Ag + +2OH - =Ag 2 O↓+H 2 O (6)
[0052] 2Ag + +2OH - + HCHO = 2Ag↓ + HCOOH + H 2 O (7)
[0053] Ag 2 O+HCOOH=2Ag↓+CO 2 ↑+H 2 O (8)
[0054] BH 4 - +2Ag 2 O=BO 2 - +4Ag↓+2H 2 ↑ (9)
[0055] First, AgNO 3 、Na 2 SiO 3Under alkaline conditions, the phase transformation of the silver salt occurs, and the soft template silver tetrasilicate is generated by double decomposition reaction (such as chemical reaction (4)). Secondly, when the reducing agent NaBH is added, 4 After that, silver tetrasilicate is reduced to generate silver atoms (as in chemical reaction (5)). Then, the intermediate product (silver tetrasilicate) in the synthesis process is used as a soft template and reacted with NaBH 4 and / or formic acid reduction to obtain a hollow porous silver skeleton. During the reaction, H 2 and / or CO 2 The release of gas causes the pores on the surface of the silver particles to become larger, eventually forming porous silver.
[0056] In addition, in an alkaline solution system, silver ions complex with hydroxyl groups to form silver oxide (Ag 2 O) Micro-nanoparticle precipitation (such as chemical reaction (6)), tiny particles of silver oxide are continuously deposited and grown, while in the reducing agent NaBH 4 Under the action of , silver ions are reduced to form silver atoms (such as chemical reaction (9)); with the extension of time, the Ostwald ripening effect causes the small particles with high surface energy and high instability to dissolve, and further provide silver sources to promote the growth of large particles, so that the surface energy of the entire particle is kept in the lowest stable state. This process makes Ag 2 The oxygen component in O is selectively removed, and the reaction is accompanied by H 2 , CO 2 The gases are released outward, that is, in the process of silver atoms gathering and growing, a silver skeleton including a porous structure is formed through the release / erosion of the gases.
[0057] That is to say, the present application introduces an auxiliary agent into the silver salt solution system through the soft template method, and the silver salt undergoes an in-situ phase transformation and generates an intermediate product, which acts as a template and continues to undergo a reduction reaction. During the process, the particles are subjected to the impact of the release / erosion of the released gas, which is the key to obtaining porous silver nanoparticles. This process omits the step of preparing the alloy precursor, which is the most demanding and time-consuming.
[0058] In addition, illustratively, in step S3, the silver source is silver nitrate, the reducing agent is sodium citrate and / or formaldehyde, glucose, hydrazine hydrate, ascorbic acid, tartrate, and the complexing agent is citric acid, and the following chemical reaction occurs with the matrix:
[0059] Ag + +C 5 H 7 O 5 COO - [Ag + ···(C 5 H 7 O 5 COO- (10)
[0060] 2OH - +2[Ag(NH 3 ) 2 + +HCHO = HCOONH 4 +2Ag↓+3NH 3 ↑+H 2 O (11)
[0061] 2[Ag(NH 3 ) 2 OH + C 6 H 12 O 6 = 2Ag + CH 2 OH(CHOH) 4 COONH + 3NH 3 +H 2 O (12)
[0062] 4Ag + +N 2 H 4 ·H 2 O = 4Ag↓+N 2 ↑+H 2 O + 4H + (13)
[0063] C 6 H 8 O 6 +2Ag + = C 6 H 6 O 6 +2Ag↓+2H + (14)
[0064] 2[Ag(NH 3 ) 2 + +2OH - = Ag 2 O + 4NH 3 +H 2 O 和 / 或,
[0065] 3Ag 2 O + C 4 H 4 O 6 2- +2OH - = 6Ag↓+2C 2 O 4 2- +3H 2 O (15)
[0066] 3Cu 2+ +2C 6 H 5 O 7 3- Cu 3 (C 6 H 5 O 7 ) 2 (16)
[0067] C 6 H 5 O 7 3- +2Ag + →C 5 H 4 O 5 2- +H + +CO 2 +2Ag↓ (17)
[0068] Cu+2Ag + 2Ag+Cu 2+ (18)
[0069] AgNO 3 First, it reacts with citrate to form a milky white silver citrate complex ([(Ag) + ···(C 5 H 7 O 5 COO - ]) (such as chemical reaction (10)), Cu and Ag + A replacement reaction occurs (such as chemical reaction (18)). Citrate and Ag + The above reaction not only reduces the free Ag in the solution, but also + concentration, and effectively reduced the Ag + The rate of reduction is reduced, and the formation and growth rate of Ag crystal nuclei are reduced (this is because when the supersaturation of the generated silver atoms is greater than its minimum supersaturation, the nucleation rate is greater than the growth rate of the crystal nucleus, that is, the amount of material consumed by crystal nucleation per unit time is greater than the amount of material consumed by crystal nucleus growth, so the growth of the crystal nucleus is inhibited; and the ion dispersion of the dilute solution is high, so the distance that the reduced silver atoms diffuse and migrate to the surface of the crystal nucleus is also greatly increased, thereby inhibiting the growth of the crystal nucleus to a certain extent), so that the Ag crystal nucleus is attached to the surface of the substrate before it grows up, which is beneficial to improve the coating situation and enhance the oxidation resistance of the material. In addition, under the synergistic effect of the complexing agent and the organic solvent, the Ag +The ability to diffuse and migrate in solution prevents Ag + During the reduction process, they swallow each other and then slow down their growth to become large particles. As a result, the crystal particles generated during the chemical plating process always maintain a small size. During the growth of the silver plating grains, the nanosilver particles are dispersed and preferentially anchored at defects such as dislocations, grain boundaries and pores, so that some defects are "healed", thereby making the surface porosity of the silver-clad copper material low and the density high.
[0070] Moreover, the preparation method of the present application not only has a dense and smooth surface of the silver-clad copper material, excellent electrical properties and broad application prospects, but also has a simple process and high safety, and is suitable for large-scale production.
[0071] In order to more effectively control the pore size and pore distribution of the silver skeleton, and more effectively control the filling rate and filling effect of the copper metal, in a preferred embodiment, the first silver salt and the second silver salt independently include one or more of silver nitrate, silver nitrite, silver acetate, silver sulfate, silver oxalate, silver methanesulfonate, silver iodide, sodium silver cyanide and dodecyl silver, and the molar concentration is 0.01-15 mol / L; and / or, the copper salt includes one or more of copper sulfate, copper chloride, copper nitrate, copper oxalate and copper acetate, and the molar concentration is 0.01-10 mol / L; and / or, the first silver salt and the second silver salt independently include one or more of silver nitrate, silver nitrite, silver acetate, and the molar concentration is 0.01-10 mol / L; and / or, The first reducing agent, the second reducing agent, and the third reducing agent independently include one or more of glucose, ascorbic acid, sodium ascorbate, citric acid, sodium citrate, formaldehyde, acetaldehyde, formic acid, acetic acid, hydrazine hydrate, sodium borohydride, sodium sulfite, sodium hypophosphite, sodium tartrate, sodium thiosulfate, and dimethylborane, with a molar concentration of 0.001 to 15 mol / L, and the dripping rate of the second reducing agent is 5 to 30 mL / min; preferably, independently, the amount of the first reducing agent, the second reducing agent, and the third reducing agent is 1 to 1.5 times the reaction stoichiometry; and / or the auxiliary agent includes Na 2 SiO 3 、Na 2 CO 3and NaCl, with a molar concentration of 0.001-15 mol / L; and / or, the first alkaline solution includes one or more of sodium hydroxide aqueous solution, potassium hydroxide aqueous solution and ammonia water, with a molar concentration of 0.01-5 mol / L; the pH of the solution system is controlled to be 5.0-14.0; and / or, the second alkaline solution includes one or more of sodium carbonate aqueous solution, sodium bicarbonate aqueous solution, potassium carbonate aqueous solution, potassium bicarbonate solution, sodium acetate aqueous solution and ammonia water, with a molar concentration of 0.01-5 mol / L; the pH of the solution system is controlled to be 5.0-14.0; the first complexing agent includes one or more of ammonia water, ethylenediamine and disodium ethylenediaminetetraacetate, monoethanolamine, diethanolamine, diisopropanolamine and N-methyldiethanolamine, with a molar concentration of 0.001-10 mol / L.
[0072] For the purpose of further optimizing the pore structure of the silver skeleton, in a preferred embodiment, in step S1, the molar ratio of the first silver salt to the auxiliary agent is (0.01-10): (0.1-15), preferably 1: (0.012-0.375); and / or, the molar ratio of the first silver salt to the dispersant is (0.01-10): (10 -5 ~5), preferably 1:(0.00116~0.1); and / or, the molar ratio of the first silver salt to the first reducing agent is (0.01~10):(10 -5 ~15), preferably 1:(0.0004~0.0083); and / or, the molar ratio of the first silver salt to the first complexing agent is (0.01~10):(0.001~10), preferably 1:(0.00083~0.0075).
[0073] In a preferred embodiment, in step S1, the preparation conditions of the first solution are: temperature of 0-80°C, rotation speed of 100-1000rpm, and time of 30-180min; and / or, adding the first alkaline solution to the first solution at a flow rate of 1-30mL / min; and / or, the first mixing time is 30-180min, the temperature is 0-80°C, the rotation speed is 100-1000rpm, and the drop rate of the additive is 1-30mL / min; and / or, the second mixing time is 30-180min. Under the above conditions, the distribution of each component is more uniform, the porosity of the silver skeleton is more suitable, and it is more conducive to the uniform distribution of copper particles in the silver skeleton.
[0074] In a preferred embodiment, in step S1, step S1 further comprises the step of freeze-drying the silver skeleton, the freeze-drying time is 6 to 24 hours, and the temperature is -50 to -60° C. Under the above conditions, it is more conducive to the free water to leave the pores of the silver skeleton, and thus more conducive to the filling of copper particles in the silver skeleton.
[0075] In the process of preparing copper particles by chemical reduction, the particle size of the grains is mainly controlled by the nucleation rate and growth rate, and different mixing methods affect the nucleation rate and growth rate. Exemplarily, in step S2, a reducing agent (ascorbic acid and / or formaldehyde and / or sodium hypophosphite and / or glucose) is added to a mixed solution of silver skeleton and copper salt, and the reduction reaction occurs evenly in the entire system at the beginning of the reaction. In the early stage of the reaction, the concentration of copper salt is high and the solution is in an oversaturated state. Under the action of the reducing agent, the copper ions in the solution system quickly aggregate to form clusters, and a large number of copper atoms are generated instantly, nucleation breaks out and a high nucleation rate is maintained; then, due to the nucleation process, Cu 2+ The consumption is large, and Cu 2+ The relatively low concentration slows down the crystal growth rate, thereby obtaining nano-copper with a smaller particle size. Under the action of capillary osmotic pressure, the nano-copper can effectively fill the pore structure of the silver skeleton to construct the matrix of the silver-coated copper material. The chemical reactions involved are as follows:
[0076] C 6 H 8 O 6 +Cu 2+ =Cu+C 6 H 6 O 6 +2H + (19)
[0077] HCHO+Cu 2+ +2OH - =Cu+HCOOH+H 2 O (20)
[0078] H 2 PO 2 - +2Cu 2+ +2H 2 O=2Cu+H 2 PO 4 - +4H + (twenty one)
[0079] CH 2 OH(CHOH) 4 CHO+Cu 2+ +2OH - =CH 2 OH(CHOH) 4 COOH+Cu+H 2 O (22)
[0080] On the basis of the above, in order to more effectively control the in-situ reduction rate and filling effect of the copper salt in the pores of the silver skeleton, in a preferred embodiment, in step S2, the molar ratio of the copper salt to the weight of the silver skeleton is (0.01~10): (0.01~15) mol / g, preferably 1: (0.5~25) mol / g; and / or, the molar ratio of the copper salt to the second reducing agent is (0.01~10): (0.1~15), preferably 1: (1~3); and / or, the molar ratio of the copper salt to the dispersant is (0.01~10): (10 -5 ~5), preferably 1:(0.0003~5).
[0081] Based on similar reasons, in a preferred embodiment, in step S2, the preparation conditions of the third solution are: temperature of 0~80°C, rotation speed of 100~500rpm, and time of 30~180min; and / or, the time of the third mixing is 30~180min; and / or, the time of the fourth mixing is 30~180min, and the temperature is 50~80°C; and / or, the reducing agent is added to the fourth solution at a drip rate of 5~30mL / min; and / or, the time of the fifth mixing is 30~180min, and the temperature is 0~80°C.
[0082] In a preferred embodiment, step S2 also includes a step of drying the substrate, the drying time is 30-180 minutes, and the temperature is 50-80°C. Under the above conditions, it is more conducive to changing the nucleation mode of the substrate surface from "uniform nucleation" to "inhomogeneous nucleation", and the nucleation rate is more significantly improved. At the same time, it can also more effectively prevent the phenomenon of silver ions swallowing each other during the reduction process to cause crystal growth. At the same time, the silver complex formed in the system can regulate Ag + The free rate in the plating solution reduces the Ag + The replacement reaction rate is more conducive to improving the uniformity of the silver layer, thereby further improving the coating and density of the silver-clad copper material.
[0083] In order to more effectively control the rate of chemical silver plating, and thus more conveniently control the thickness of the silver layer and further improve the uniformity of the silver layer, in a preferred embodiment, in step S3, the second complexing agent includes a main complexing agent and an optional secondary complexing agent, the main complexing agent includes one or more of ammonia water, ethylenediaminetetraacetic acid, ethylenediamine, polyethylene glycol, diethylenetriamine, polyethylene glycol, triethylenetetramine, triethanolamine, polyethylenepolyamine and succinimide, and the molar ratio of the second silver salt to the main complexing agent is (0.01~10):(0.001~10), preferably 1:(0.25~1); the secondary complexing agent includes polydopamine, hydantoin, imidazole, citric acid, sodium citrate, tartaric acid, oleic acid, oleamide, ascorbic acid, sodium pyrophosphate, aminocarboxylic acid, One or more of 1,3-diketone, hydroxycarboxylic acid and polyamine, the molar ratio of the second silver salt to the secondary complexing agent is (0.01-10): (0-10), preferably 1: (0.25-2); and / or, the ratio of the mass of the substrate to the molar amount of the second silver salt is (0.01-10): (0.01-15) g / mol, preferably 1: (0.02-0.4) g / mol; and / or, the ratio of the mass of the substrate to the molar amount of the second complexing agent is (0.01-10): (0.001-10) g / mol; and / or, the ratio of the mass of the substrate to the molar amount of the third reducing agent is (0.01-10): (0.1-15) g / mol, preferably 1: (0.4-1.512) g / mol.
[0084] In a preferred embodiment, in step S3, the fifth solution is added at a dripping rate of 5-30 mL / min to perform a sixth mixing with the substrate; and / or the sixth mixing temperature is 0-80° C. and the time is 30-180 min. Under the above conditions, the nucleation rate of the silver layer is more suitable and the quality is more stable.
[0085] In order to further improve the purity of the silver-coated copper material, step S3 also includes washing the silver-coated copper material until the conductivity of the silver-coated copper material washing mother liquor is ≤20 μS / cm, and then performing a drying step.
[0086] In order to make the solubility between the components higher and the dispersion more uniform, in a preferred embodiment, the first solution, the second solution, the third solution, and the fifth solution independently include an organic solvent and water, and the organic solvent independently includes one or more of methanol, ethanol, propanol, ethylene glycol, isopropanol, acetone, N,N-dimethylformamide, N,N-dimethylacetamide and diethylformamide, and the molar concentration is 0.001~10mol / L; and / or, independently, the first solution, the second solution, the third solution, and the fifth solution include a dispersant, and the dispersant independently includes one or more of polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone, methylcellulose, polyacrylic acid, sodium sulfosuccinate, sodium lauryl sulfate, sodium dodecyl sulfonate, Tween 80, sodium stearate, ethanolamine, fatty alcohol polyoxyethylene ether, octylphenol polyoxyethylene ether 10, dodecyl tetraethylene glycol ether and nonylphenol polyoxyethylene ether 10, and the molar concentration is 10 -5 ~5mol / L.
[0087] In another typical embodiment of the present invention, the application of the silver-coated copper material in the photovoltaic and electronic industries is also provided. When the silver-coated copper material is used in the photovoltaic and electronic industries, the cost of raw materials can be significantly reduced and the service life of the raw materials can be increased.
[0088] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0089] Example 1
[0090] The schematic diagram of the preparation process of silver-clad copper material is shown in Figure 1 .
[0091] Step S1, silver salt (silver nitrate, 2000mL, concentration of 1.5mol / L), dispersant (3.5mmol, polyvinyl pyrrolidone), organic solvent (ethanol, volume of 500mL, concentration of 5mol / L) were dispersed and reacted at 30°C and magnetic stirring at 300rpm for 180min to obtain a first solution; 15mol / L of auxiliary agent (75mL of Na 2 SiO 3 ), alkaline solution (NH 4 OH+NaOH, 30mL, OH - The concentration of the first solution was 5 mol / L, and the pH of the first solution was adjusted to 5.0), stirring was continued for 30 min, and then centrifuged to obtain white silver-containing solid particles (Ag 10 Si 4 O 13 Powder particles), and 5g of Ag 10 Si4 O 13 The powder particles were added into 1000 mL of 5 mol / L ethanol solvent for solid-liquid mixing to form a uniformly dispersed suspension;
[0092] Then, 5 mL of reducing agent (NaBH 4 , controlling its molar concentration to be 5 mol / L), a second solution of a complexing agent (ammonia water, controlling its molar concentration to be 0.5 mol / L) and an organic solvent (ethanol) is added dropwise into the above solution system, and stirring is continued for 60 min. After the reaction is sufficient, filtering, washing, and freeze-drying at -60°C for 12 h to obtain a silver skeleton 1 with holes;
[0093] Step S2, copper salt (0.2 mol CuSO 4 ·5H 2 O), solvent (30 ° C, ethanol and deionized water, the volume ratio of the two is 1:1, and the Cu 2+ ), a dispersant (0.06 mmol, polyvinyl pyrrolidone), dispersed at 30° C. and 300 rpm with magnetic stirring for 180 min to obtain a third solution;
[0094] 2.5 g of silver skeleton was added to 2000 mL of the third solution (the volume ratio of ethanol to deionized water was 1:1), and then an alkaline aqueous solution (2 mol / L NaOH and 1 mol / L NH 4 ·H 2 O) controlling the pH to 5.0, and performing an immersion adsorption reaction for 180 minutes under the conditions of magnetic stirring at 300 rpm and a water bath temperature of 60°C; after the reaction is sufficient, a reducing agent (a molar ratio of ascorbic acid to copper salt is 3:1) is dripped into the above reaction system at a dripping rate of 5 mL / min through a peristaltic pump, and an in-situ reduction reaction is performed at 50°C for 180 minutes; after the reaction is completed, filtering, washing with anhydrous ethanol, and vacuum drying at 60°C for 180 minutes to obtain a matrix 3 including copper particles 2;
[0095] Step S3, dispersing 2.5 g of the matrix in 1000 mL of a mixed solvent system including a solvent (800 mL of deionized water, 200 mL of ethanol) and a secondary complexing agent (ascorbic acid, with the molar ratio of silver salt to secondary complexing agent being controlled to be 1:0.25);
[0096] Mix silver salt (silver nitrate, the concentration of which is controlled to be 0.05 mol / L) and solvent (ethylene glycol 200 mL, ethanol 200 mL, deionized water 600 mL). After the silver nitrate is completely dissolved, slowly add the main complexing agent (ammonia water, the molar ratio of silver salt to the main complexing agent is controlled to be 1:0.25) while stirring, so that the silver nitrate solution just presents a transparent liquid without precipitation, and obtains a silver ammonia solution; add a reducing agent (1.26 mol / L formaldehyde 3.0 mL) to the solvent (450 mL deionized water, 450 mL ethanol), mix, and dropwise add it to the reaction system including the substrate and the silver ammonia solution at a flow rate of 5 mL / min, and then Then, chemical silver plating is performed on the outer surface of the substrate at 30°C and magnetic stirring at 300 rpm. In this process, the silver particles 4 have good wettability with the exposed silver skeleton of the substrate, which is convenient for bonding with the atoms of the substrate and extending and spreading in a two-dimensional layered mode. At the same time, the reduced silver atoms are induced to first aggregate into epitaxial layered / island-like silver particles 5, and then a silver coating 6 is obtained on the surface of the substrate. After reacting for 180 minutes, the silver particles are separated in turn and washed with an ethanol solvent containing a dispersant (polyvinyl pyrrolidone), and the conductivity of the washing mother liquor is controlled to be ≤20μS / cm. The collected samples are vacuum dried at 60°C for 180 minutes to obtain a silver-coated copper material 7.
[0097] SEM images of silver-clad copper materials are shown in Figure 2 As can be seen from the figure, the surface of the silver-coated copper material particles is round and smooth, spherical or quasi-spherical, with good particle dispersion and relatively uniform particle size, and the average particle size is about 2.7μm. The growth mechanism of the silver-coated copper material is as follows: in the early stage of the reaction, during the deposition process, silver nanocrystals are adsorbed on the activated position of the exposed metal surface of the matrix silver skeleton; at the same time, the small-sized nanosilver particles effectively fill the pores and holes between the grains, that is, on the limited surface of the silver skeleton, a small amount of silver atoms grow to form small particle crystals, while a large number of silver atoms gather on the surface of the copper atoms to form many extremely small crystals (Ag + Replacement reaction with nano copper Cu+ 2Ag + =2Ag+Cu 2+ ). When silver atoms generate crystal nuclei on the surface of copper atoms, the silver atoms generated later are quickly deposited close to the surface of copper atoms at the edge of the crystal nuclei. The nano silver crystal nuclei quickly grow into large crystals, and the crystals are tightly connected together to quickly form a dense silver coating. The surface of the coating is smooth and flat, so the overall density is improved.
[0098] The specific surface area of the silver skeleton in the silver-clad copper material is shown in Figure 3 The adsorption isotherm shows a typical IV type, indicating that it is mainly composed of mesoporous (30-50 nm) structures. 2 The adsorption-desorption isotherm is in the high pressure section (P / P 0>0.9) has a significant jump due to the macroporous structure; calculated by the BET model, the specific surface area of the silver skeleton is 25.72m 2 / g.
[0099] The pore size distribution of the silver skeleton in the silver-clad copper material is shown in Figure 4 As can be seen from the figure, the pore size of the silver skeleton prepared in Example 1 is in the range of 30-50nm for mesopores and 50-90nm for macropores. Calculated by the BJH model, the average pore size of the silver skeleton is 50.23nm. The silver skeleton at this pore size provides a nucleation site for nano-copper; in addition, the synergistic effect of the various components in the material not only solves the problem of high activity and easy oxidation of copper particles, but also through the rich pore structure of the silver skeleton, under the confining effect of spatial physical pores, during the outer silver plating process, the dissolution of copper can be significantly reduced, and the negative effect of copper particles on the plating stage can be limited.
[0100] Example 2
[0101] The only difference from Example 1 is:
[0102] Step S1, silver salt (silver sulfate, 2000mL, concentration of 1mol / L), dispersant (0.2mol, ethylene glycol), organic solvent (1.5mol / L, 500mL of N,N-dimethylacetamide) were dispersed and reacted at 50°C and magnetic stirring at 200rpm for 120min to obtain a first solution; 2mol / L of auxiliary agent (15mL, Na 2 SiO 3 ), 2 mL of 1.5 mol / L alkaline solution (NaOH, pH adjusted to 10.0), continued stirring for 30 min, and then centrifuged to obtain a white silver-containing solid (Ag 10 Si 4 O 13 Powder particles), and 5g of Ag 10 Si 4 O 13 The powder particles were added into 1000 mL of an aqueous solvent having a molar concentration of 1.5 mol / L ethylene glycol, and solid-liquid mixing was performed to form a uniformly dispersed suspension;
[0103] Then, 10 mL of a second solution including a reducing agent (glucose, concentration of 1.0 mol / L), a complexing agent (ammonia water, concentration of 1.5 mol / L) and an organic solvent (N,N-dimethylacetamide, concentration of 1.5 mol / L) was added dropwise into the above solution system through a peristaltic pump and stirred for 30 minutes. After the reaction was sufficient, the solution was filtered, washed, and freeze-dried at -50°C for 6 hours to obtain a silver skeleton with holes.
[0104] Example 3
[0105] The only difference from Example 1 is:
[0106] Step S1, dispersing and reacting silver salt (silver acetate, 1000mL, concentration of 2.5mol / L), dispersant (0.1mol, sodium dodecyl sulfate), and organic solvent (1mol / L, 500ml propanol) at 50°C and magnetic stirring at 500rpm for 30min to obtain a first solution; dripping 1mol / L auxiliary agent (30mL, NaCl) and 5mL alkaline solution (ammonia water, pH adjusted to 8.0) with a concentration of 0.28mol / L through a peristaltic pump at a flow rate of 30mL / min, continuing stirring for 180min, and then centrifuging to obtain a white silver-containing solid (AgCl powder particles), and adding 5g of the AgCl powder particles to 1000mL of ethylene glycol solvent with a concentration of 2.5mol / L, performing solid-liquid mixing to form a uniformly dispersed suspension;
[0107] Then, 10 mL of a second solution including a reducing agent (ascorbic acid, concentration of 0.1 mol / L), a chelating agent (ethylenediaminetetraacetic acid, concentration of 1.0 mol / L) and an organic solvent (propanol) was added dropwise into the above solution system through a peristaltic pump and stirred continuously for 180 min. After the reaction was sufficient, the solution was filtered, washed and freeze-dried at -60 °C for 24 h to obtain a silver skeleton with holes.
[0108] Example 4
[0109] The only difference from Example 1 is:
[0110] Step S2, copper salt (copper chloride, the molar concentration of which is controlled to be 0.1 mol / L), solvent (1000 mL, isopropanol and water in a volume ratio of 1:1), and dispersant (0.5 mol / L, polyethylene glycol) are mixed, and dispersed at 30° C. and 500 rpm with magnetic stirring for 30 minutes to obtain a third solution;
[0111] 2.5 g of silver skeleton was added to 500 mL of the third solution (the volume ratio of ethanol to deionized water was 1:1), and then an alkaline aqueous solution (0.01 mol / L KOH and 0.1 mol / L NH 4 ·H 2O) control the pH to 12.0, and perform the adsorption reaction for 30 minutes under magnetic stirring at 300 rpm and 60°C. After the reaction is sufficient, a reducing agent (glucose, with a molar ratio of 1:1 to copper salt) is dripped into the above reaction system at a flow rate of 5 mL / min through a peristaltic pump, and an in-situ reduction reaction is performed at 60°C for 180 minutes. After the reaction is completed, the substrate is filtered, washed with anhydrous ethanol, and vacuum dried at 60°C for 180 minutes to obtain a matrix.
[0112] Example 5
[0113] The only difference from Example 1 is:
[0114] Step S2, copper salt (copper acetate, the molar concentration of which is controlled to be 5 mol / L), solvent (1000 mL, N,N-dimethylacetamide and water in a volume ratio of 1:1), and dispersant (0.5 mol / L, polyacrylic acid) are mixed, and dispersed at 30° C. and 100 rpm with magnetic stirring for 180 min to obtain a third solution;
[0115] 2.5 g of silver skeleton was added to 200 mL of the third solution at a volume ratio of 1:1, and then an alkaline aqueous solution (0.01 mol / L NaOH and 0.1 mol / L NH 4 ·H 2 O) control the pH to 14.0, and carry out immersion adsorption reaction for 180 minutes under magnetic stirring at 300 rpm and 60°C; after the reaction is sufficient, a reducing agent (formaldehyde, with a molar ratio of 1:1 to copper salt) is dripped into the above reaction system at a flow rate of 30 mL / min through a peristaltic pump, and an in-situ reduction reaction is carried out at 60°C for 30 minutes; after the reaction is completed, the reaction is filtered, washed with anhydrous ethanol, and vacuum dried at 80°C for 30 minutes to obtain a matrix.
[0116] Example 6
[0117] The only difference from Example 1 is:
[0118] Step S3, dispersing 2.5 g of the matrix in 1000 mL of a mixed solvent system including a solvent (300 mL of deionized water, 700 mL of ethanol), a secondary complexing agent (disodium ethylenediaminetetraacetic acid, with the molar ratio of silver salt to secondary complexing agent controlled to be 0.5:1), and a dispersant (polyvinyl pyrrolidone, with the content controlled to be 0.5 mol / L);
[0119] Mix silver salt (silver sulfate, the concentration of which is controlled to be 1.0 mol / L) and solvent (ethylene glycol and deionized water in a volume ratio of 1:1, 1000 mL), and after the silver sulfate is fully dissolved, slowly add the main complexing agent (ethylenediaminetetraacetic acid, the molar ratio of silver salt to the main complexing agent is controlled to be 1:1) while stirring until the silver sulfate solution just appears as a transparent liquid without precipitation, to obtain a mixed solution; add a reducing agent (glucose, the concentration is 1 mol / L) to the solvent (200 mL water, 800 mL ethanol), and mix;
[0120] Then, at 50° C. and 300 rpm of magnetic stirring, the mixture was added dropwise at a rate of 5 mL / min into the mixed solvent system including the substrate and the silver salt, and chemical silver plating was performed on the outer surface of the substrate; after reacting for 30 minutes, the mixture was separated in turn and washed with an ethanol solvent containing a dispersant (0.001 mol / L of sodium stearate), and the conductivity of the washing mother liquor was controlled to be ≤20 μS / cm; the collected samples were vacuum dried at 60° C. for 180 minutes to obtain a silver-clad copper material.
[0121] Example 7
[0122] The only difference from Example 1 is:
[0123] Step S3, dispersing 2.5 g of the matrix in 1000 mL of a mixed solvent system including a solvent (600 mL of deionized water, 400 mL of ethanol), a secondary complexing agent (tartaric acid, controlling the molar ratio of silver salt to secondary complexing agent to be 0.5:1), and a dispersant (methyl cellulose, controlling its content to be 0.8 mol / L);
[0124] Mix silver salt (silver acetate, the concentration of which is controlled to be 0.8 mol / L) and solvent (ethylene glycol, ethanol, deionized water in a volume ratio of 1:3:6, 1000 mL), and after the silver acetate is fully dissolved, slowly add a main complexing agent (diethylenetriamine, the molar ratio of silver salt to the main complexing agent is controlled to be 1:0.8) while stirring until the silver acetate solution just appears as a transparent liquid without precipitation, to obtain a mixed solution; add a reducing agent (ascorbic acid, the molar concentration is 1 mol / L) to the solvent (350 mL water, 650 mL ethanol), and mix;
[0125] Then, at 80°C and magnetic stirring at 300 rpm, it was added dropwise at a flow rate of 30 mL / min into the mixed solvent system including the substrate and the silver salt, and chemical silver plating was performed on the outer surface of the substrate; after reacting for 15 minutes, it was separated in turn and washed with an ethanol solvent containing a dispersant (0.001 mol / L methyl cellulose) to obtain a mother liquor conductivity of ≤20 μS / cm, and the collected samples were vacuum dried at 60°C for 180 minutes to obtain a silver-clad copper material.
[0126] Comparative Example 1
[0127] The only difference from Example 1 is:
[0128] In step S2, no alkaline solution is added to the third solution of copper salt.
[0129] Comparative Example 2
[0130] The only difference from Example 1 is:
[0131] In step S3, the second complexing agent is not added.
[0132] Comparative Example 3
[0133] The only difference from Example 1 is:
[0134] Step S1 is not included.
[0135] According to analysis, during the silver plating process, defects on the surface of copper particles will cause silver nuclei to start growing first. At the same time, when no alkaline solution and complexing agent are added, the silver particles will be deposited on the surface of the nano-copper particles first because of the high Gibbs free energy and strong surface adsorption force, causing the silver particles previously coated on the surface of the copper particles and the copper particles that have not been coated to form micro-batteries in the plating solution. Under the action of the micro-battery, the silver coating is not uniform, thereby reducing the oxidation resistance and conductivity of the silver-coated copper material. In addition, during the silver plating reaction process, the alkaline environment in the solution also affects the coordination of silver ions in the solution, that is, the stability of the plating solution.
[0136] In addition, the plating effect depends on the binding force between the complex ions. When no complexing agent is added, it is difficult for silver ions to form cationic complexes, which weakens the binding force and causes the chemical reaction rate to be too fast. Some silver ions are released from the plating solution and undergo a replacement reaction with copper; some silver ions are directly reduced in the solution but cannot be deposited on the surface of the substrate, resulting in the silver plating effect not being able to achieve good coating.
[0137] The characterization parameters and test results of the silver-clad copper materials prepared in the above examples and comparative examples are shown in Table 1.
[0138] Test method:
[0139] The weight of copper particles in the silver-coated copper material: by the difference method, that is, first weigh the total weight m of the matrix of the silver-coated copper material 1 Then the silver content is measured and analyzed by chemical precipitation method. The matrix is dissolved and diluted with concentrated nitric acid, and then a small excess of NaCl dilute solution is used to precipitate. After the precipitation is complete, it is diluted with water, filtered, and washed. After it is fully dried, the precipitate mass m is weighed with an electronic balance. 2 , Silver content W Ag The calculation method of is as follows: , through differential calculation, the copper particle weight W Cu =m 1 -W Ag .
[0140] The oxidation resistance of silver-clad copper materials is mainly determined by the silver content and uniformity of the surface coating. The larger the coating area and the more uniform the coating, the better the oxidation resistance of the material. t To characterize the oxidation resistance of the material, the formula W t = [(m 2 -m 1 ) / m 1 ] × 100% for numerical calculation. 1 ) was placed in a muffle furnace, heated to 500°C, kept constant in air for 30 min, and weighed after cooling (denoted as m 2 ). A small weight gain rate means that the oxidation degree of the silver-clad copper material at high temperature is low, indicating good oxidation resistance; otherwise, it means poor oxidation resistance.
[0141] Conductive performance test: Grind the silver-coated copper material and the organic carrier evenly (the solvent of the organic carrier is mainly composed of pine alcohol, butyl carbitol, butyl carbitol acetate, hydrogenated castor oil, ethyl cellulose, ethanol, tributyl citrate, and the specific content ratio (wt%) of each component is 45:22.5:7.5:3:6:9:7), heat in a water bath at 60°C, stir for 2h until dissolved and keep warm for 1h, cool at room temperature, measure 30wt% organic carrier and 70wt% silver-coated copper material, grind until uniform, and obtain conductive slurry. Apply it evenly on a glass slide by drop coating, sinter at 200°C for 30min, cool to room temperature, and test with a SZT-B four-probe tester.
[0142] Table 1
[0143]
[0144] According to the analysis, in the embodiment of the present invention, the silver skeleton has a large specific surface area and pore size (average pore size 39.83~50.23nm), the copper particles have a large particle size, and the prepared silver-coated copper material has a low weight gain rate, which is stable at 8.41%~8.77%. This is because the porous silver skeleton provides effective filling space and abundant nucleation sites for the copper particles, promotes the uniform coating of the silver layer, reduces the tendency of silver agglomeration and copper oxidation, and thus reduces the additional weight gain of the silver-coated copper material. On the contrary, in the comparative example, the particle size of the copper particles is small, the specific surface area and pore size of the silver skeleton (average pore size 34.11~33.86nm) are small, and the weight gain rate of the silver-coated copper material is increased to 8.89%~9.96%. The reason is that the surface active sites of the small-size copper particles are more dense, which promotes the rapid deposition of silver atoms and causes the agglomeration of the silver layer, and the density of the silver layer is relatively low, making the copper easier to oxidize in the subsequent high-temperature treatment, and the weight gain rate is high.
[0145] In addition, it can be seen that the greater the weight of the matrix silver skeleton, the smaller the specific surface area of the silver skeleton, and the lower the amount of copper particles filled; at the same time, as the specific surface area of the silver skeleton decreases, the exposed silver skeleton can provide fewer active sites for the nucleation of silver nanocrystals during the deposition process of the coating, and the nucleation rate of the coating is lower, which leads to poor density and uniformity of the coating and reduced conductivity of the material.
[0146] Compared with the comparative example, the embodiment of the present invention optimizes the matrix structure of the silver-coated copper material, that is, the silver skeleton has holes and copper particles. In the process of chemical silver plating, the exposed silver skeleton increases the active site for the nucleation of silver nanocrystals, reduces the overpotential of the Ag nucleation reaction, thereby increasing the nucleation rate and grain refinement, and strengthening the coating, and the coating is fine and uniform. Therefore, the plated surface is continuously enriched with nanosilver particles, which serve as new active sites for the nucleation of silver nanocrystals, effectively inhibiting the growth of the original crystal silver particles (that is, in the early stage of the silver plating reaction, the silver nanoparticles are generated less, and the coating is deposited on the surface of the substrate in a layered growth mode; when the reaction proceeds to the middle and late stages, a large number of generated silver nanoparticles are continuously deposited and aggregated, and the growth mode of the silver coating is transformed from layered to island growth, so that the isolated island structure extends and grows along the edge, and gradually connects to each other into sheets to form a multi-layer stacking structure); as a result, the silver nanocrystal particles generated in the chemical plating always maintain a small size. At the same time, due to the small size of nanosilver particles, they are dispersed during the growth of silver grains and are preferentially anchored at defects such as dislocations, grain boundaries and pores, thereby refining the grains of the silver plating. This can effectively improve the coating effect of the plating and increase the density. During the sintering process, the oxidation process is prevented from proceeding from the surface of the film to the inside of the film, thereby improving the material's oxidation resistance and electrical conductivity.
[0147] In addition, it can be seen that when all process parameters are within the preferred range of the present invention, the raw material cost of the silver-clad copper material is lower, the density and uniformity of the plating layer are better, and the oxidation resistance and conductivity are better.
[0148] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A silver-clad copper material, characterized in that: include: A substrate and a silver layer coated on the surface of the substrate, The matrix includes copper particles and a silver skeleton, the silver skeleton has holes, and the copper particles are distributed in the holes of the silver skeleton. The silver layer is prepared by chemical plating.
2. The silver-clad copper material according to claim 1, characterized in that: In the silver-clad copper material, The diameter of the copper particles is 1-100 nm; and / or, The weight percentage of the copper particles is 5-50%; and / or, The weight ratio of the copper particles to the silver skeleton is (0.1-2.5): (0.5-5); and / or, The pores in the silver skeleton have a pore size of 5-100 nm and a specific surface area of 10-300 m 2 / g.
3. The silver-clad copper material according to claim 1 or 2, characterized in that: In the silver-clad copper material, The weight ratio of the substrate to the silver layer is (1-15):(0.1-5).
4. The method for preparing the silver-clad copper material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step S1, performing a first mixing of a first solution including a first silver salt, an auxiliary agent, and a first alkaline solution to obtain silver-containing solid particles, and performing a second mixing of the silver-containing solid particles with a second solution including a first reducing agent and a first complexing agent to obtain a silver skeleton having pores; Step S2, performing a third mixing of the silver skeleton and a third solution including a copper salt, then adding a second alkaline solution and performing a fourth mixing to obtain a fourth solution, then adding a second reducing agent and performing a fifth mixing to fill copper particles in the pores of the silver skeleton to obtain a matrix; Step S3, mixing the substrate with a fifth solution including a second silver salt, a second complexing agent and a third reducing agent for a sixth time to perform chemical silver plating to obtain the silver-clad copper material.
5. The preparation method according to claim 4, characterized in that: Independently, the first silver salt and the second silver salt include one or more of silver nitrate, silver nitrite, silver acetate, silver sulfate, silver oxalate, silver methanesulfonate, silver iodide, sodium silver cyanide and dodecyl silver, and the molar concentration is 0.01-15 mol / L; and / or, The copper salt includes one or more of copper sulfate, copper chloride, copper nitrate, copper oxalate and copper acetate, with a molar concentration of 0.01-10 mol / L; and / or, Independently, the first reducing agent, the second reducing agent, and the third reducing agent include one or more of glucose, ascorbic acid, sodium ascorbate, citric acid, sodium citrate, formaldehyde, acetaldehyde, formic acid, acetic acid, hydrazine hydrate, sodium borohydride, sodium sulfite, sodium hypophosphite, sodium tartrate, sodium thiosulfate, and dimethylborane, with a molar concentration of 0.001-15 mol / L; and / or, The auxiliary agent includes one or more of Na2SiO3, Na2CO3 and NaCl, with a molar concentration of 0.001-15 mol / L; and / or, The first alkaline solution comprises one or more of a sodium hydroxide aqueous solution, a potassium hydroxide aqueous solution and ammonia water, with a molar concentration of 0.01-5 mol / L, and the pH of the first solution is controlled to be 5.0-14.0; and / or, The second alkaline solution comprises one or more of sodium carbonate aqueous solution, sodium bicarbonate aqueous solution, potassium carbonate aqueous solution, potassium bicarbonate solution, sodium acetate aqueous solution and ammonia water, with a molar concentration of 0.01-5 mol / L, and the pH of the fourth solution is controlled to be 5.0-14.0; and / or, The first complexing agent includes one or more of ammonia water, ethylenediamine, disodium ethylenediaminetetraacetate, monoethanolamine, diethanolamine, diisopropanolamine and N-methyldiethanolamine, and the molar concentration is 0.001-10 mol / L.
6. The preparation method according to claim 4, characterized in that: In the step S1, The molar ratio of the first silver salt to the auxiliary agent is (0.01-10): (0.1-15); and / or, The molar ratio of the first silver salt to the first reducing agent is (0.01-10): (10 -5 ~15); and / or, The molar ratio of the first silver salt to the first complexing agent is (0.01-10): (0.001-10).
7. The preparation method according to claim 4, characterized in that: In the step S1, The first mixing time is 30-180 min, the temperature is 0-80° C., the rotation speed is 100-1000 rpm, and the drop rate of the auxiliary agent is 1-30 mL / min; and / or, The second mixing time is 30 to 180 minutes.
8. The preparation method according to claim 4, characterized in that: The step S1 also includes the step of freeze-drying the silver skeleton, wherein the freeze-drying time is 6 to 24 hours and the temperature is -50 to -60°C.
9. The preparation method according to claim 4, characterized in that: In the step S2, The molar ratio of the copper salt to the weight of the silver skeleton is (0.01-10): (0.01-15) mol / g; and / or, The molar ratio of the copper salt to the second reducing agent is (0.01-10): (0.1-15).
10. The preparation method according to claim 4, characterized in that: In the step S2, The third mixing time is 30 to 180 minutes; and / or, The fourth mixing time is 30 to 180 minutes; and / or, The fifth mixing process is performed for 30 to 180 minutes at a temperature of 0 to 80°C.
11. The preparation method according to claim 4, characterized in that: The step S2 also includes a step of drying the substrate, wherein the drying time is 30-180 minutes and the temperature is 50-80°C.
12. The preparation method according to claim 4, characterized in that: In the step S3, The second complexing agent includes a main complexing agent and an optional secondary complexing agent, wherein the main complexing agent includes one or more of ammonia water, ethylenediaminetetraacetic acid, ethylenediamine, diethylenetriamine, polyethylene glycol, triethylenetetramine, triethanolamine, polyethylenepolyamine and succinimide, and the molar ratio of the second silver salt to the main complexing agent is (0.01-10): (0.001-10); the secondary complexing agent includes one or more of polydopamine, hydantoin, imidazole, citric acid, sodium citrate, tartaric acid, oleic acid, oleamide, ascorbic acid, sodium pyrophosphate, aminocarboxylic acid, 1,3-diketone, hydroxycarboxylic acid and polyamine, and the molar ratio of the second silver salt to the secondary complexing agent is (0.01-10): (0-10); and / or, The ratio of the mass of the matrix to the molar amount of the second silver salt is (0.01-10): (0.01-15) g / mol; and / or, The ratio of the mass of the matrix to the molar amount of the second complexing agent is (0.01-10): (0.001-10) g / mol; and / or, The ratio of the mass of the substrate to the molar amount of the third reducing agent is (0.01-10): (0.1-15) g / mol.
13. The preparation method according to claim 4, characterized in that: In the step S3, The sixth mixing temperature is 0-80°C and the time is 30-180 min; and / or, The step S3 further comprises washing the silver-coated copper material until the conductivity of the silver-coated copper material washing mother liquor is ≤20 μS / cm, and then performing a drying step.
14. The preparation method according to claim 4, characterized in that: Independently, the first solution, the second solution, the third solution, and the fifth solution comprise an organic solvent and water, wherein the organic solvent comprises one or more of methanol, ethanol, propanol, ethylene glycol, isopropanol, acetone, N,N-dimethylformamide, N,N-dimethylacetamide, and diethylformamide, and the molar concentration is 0.001-10 mol / L; and / or, Respectively and independently, the first solution, the second solution, the third solution, and the fifth solution include a dispersant, and the dispersant includes one or more of polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone, methyl cellulose, polyacrylic acid, sodium sulfosuccinate, sodium lauryl sulfate, sodium lauryl sulfonate, Tween 80, sodium stearate, ethanolamine, fatty alcohol polyoxyethylene ether, octylphenol polyoxyethylene ether 10, dodecyl tetraethylene glycol ether, and nonylphenol polyoxyethylene ether 10, with a molar concentration of 10 -5 ~5mol / L.
15. Application of the silver-clad copper material according to any one of claims 1 to 3 in the fields of photovoltaic and electronic industries.
Citation Information
Patent Citations
Silver-containing plating solution and preparation method of foam metal material
CN112853409A
Preparation method of silver-coated copper powder, silver-coated copper powder and application of silver-coated copper powder
CN118218588A